Pengaruh Perbandingan Komposisi Bahan Baku terhadap Kualitas dan Lama Waktu Pengomposan - I Ketut Merta Atmaja; I Wayan Tika; I Made Anom. S Wijaya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The rice biomass potential of red rice (local varieties) such as rice straw and chicken manure can be utilized as a raw material for composting. This research aimed to determine the best composition ratio of compost raw materials and to find the minimum time to produce compost with such quality. This research used a treatment composition ratio of rice straw and chicken manure where P1 = (6 : 8), P2 = (6 : 7), P3 = (6 : 6), P4 = (6 : 5), and P5 = (6 : 4 ). The dimension of composting pile were 1 m length, 1 m height, and 1 m wide. Each treatment material assumed 50 kg. Piles of compost material in each treatment were covered using a tarp to keep the temperature and protect from outside interference during the composting process. The parameters measured were temperature, moisture content, yield, pH, nitrogen, carbon, and C/N ratio. The composting process lasted for 78 days with temperature ranged 30,1 – 51,1°C. Compost moisture ranged from 31,74 – 32,59%. Compost yield ranged 59 -64%, and pH ranged between 7,2 – 7,5. In general, the quality of the produced compost accordance to SNI 19-7030-2004 with a final C/N ratio was 16 - 33. The P1 which have composition ratio of rice straw and chicken manure 6 : 8 was the best treatment which have C/N ratio of 16 and for 63 days of composting process.